2017
DOI: 10.15376/biores.12.4.8704-8724
|View full text |Cite
|
Sign up to set email alerts
|

A post-occupancy evaluation of the influence of wood on environmental comfort

Abstract: Emerging research on the impact of interior finishes, more specifically wood, is beginning to shed light on informed design opportunities. As a natural building material with unique features, wood creates warm and pleasant atmospheres and has the potential of enhancing the well-being of occupants. This research attempted to better understand how occupants perceive wood in built environments and whether its indoor use influenced the satisfaction of occupants. The comfort of occupants may have been influenced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…This result supported the hypothesis set forth in H1 : “Respondents will perceive, and evaluate the environmental factors of a space using laminated wood beams more positively compared to spaces using post-tensioned concrete beams, and steel beams”. These results support the results obtained previously from the studies – Aydıntan (2001), Burnard and Kutnar (2015), Fujisaki et al (2015), Kır (2015), Poirier et al (2019), Watchman et al (2017) and Shen et al (2021). The spaces using laminated wooden beams and steel beams were perceived as broader and larger compared to the spaces using post-tensioned concrete beams.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…This result supported the hypothesis set forth in H1 : “Respondents will perceive, and evaluate the environmental factors of a space using laminated wood beams more positively compared to spaces using post-tensioned concrete beams, and steel beams”. These results support the results obtained previously from the studies – Aydıntan (2001), Burnard and Kutnar (2015), Fujisaki et al (2015), Kır (2015), Poirier et al (2019), Watchman et al (2017) and Shen et al (2021). The spaces using laminated wooden beams and steel beams were perceived as broader and larger compared to the spaces using post-tensioned concrete beams.…”
Section: Resultssupporting
confidence: 90%
“…The transitions of materials, the intersecting points, the relationships of emptiness and fullness, and the colour attributes can create different influences on users. Studies conducted in this area (Burnard and Kutnar, 2015; Fujisaki et al , 2015; Garip and Seymen, 2021; Ikei and Miyazaki, 2020; Kır, 2015; Poirier et al , 2019; Shen et al , 2021; Watchman et al , 2017) reported that many attributes of the type of materials used in interior spaces, such as colour, texture, relationship with environment and light, affect spatial perception. The careful and correct selection of each building material in interior design is particularly important for obtaining the expected features from the surfaces formed in the space.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, some authors only carried out qualitative evaluations, as follows: the authors of [ 135 ] analyzed the relationship between defects and occupant satisfaction and loyalty in build-then-sell houses; the authors of [ 86 ] assessed how maintenance features might affect occupant satisfaction; the authors of [ 71 ] analyzed the demand for space in the common areas of student residences in Iran; the authors of [ 153 ] applied the POE to understand how occupants perceive wood in built environments; the authors of [ 129 ] analyzed how the social dimension of physical space in educational contexts can explain a student’s academic achievement.…”
Section: Resultsmentioning
confidence: 99%